ODEL PENGEMBANGAN PARIWISATA BAHARI BERBASIS MASYARAKAT DI KABUPATEN HALMAHERA UTARA - Aderius Sero (Pusat Studi Pariwisata Universitas Gadjah Mada, 2012)
This research aimed to (1) study perception of people and private institution on maritime tourism development in Tagalaya, Kumo and Kakara in North Halmahera regency and (2) to study implementation of the community based maritime tourism development in Tagalaya, Kumo and Kakara in North Halmahera regency.It used descriptive method to describe and analyze perception and participation and people empowerment activity. It used qualitative approach, which result in descriptive data in form of written or oral words of observed people. The processed data was then discussed systematically to get picture of the condition with final results of conclusion. Data was collected through in-depth interview, observation and documentation with informants of people, government, and administrator of tourism resorts selected purpo-sively.Results of the research indicated that first: people perceive the development model as providing work. They perceived tourism facility should be improved. About human re-sources, they perceive that it was very supporting. In addition they perceive manage-ment of the tourism object is low indicated with less optimal service level. Moreover, promotion was required with improvement of the resorts first. Second: people in the three tourism resorts participated in the maritime tourism development. The participa-tion was in attending meeting, dissemination, security and order/cleanness. Their contri-bution was manifested in form as management of tourism object, establishing food shop, providing home stay, preparing maritime transportation, doing tourism infrastructure development project in the resorts and cooperating with private sectors. Community empowerment was done through development of tourism village by government of ad-ministrator through training and education, dissemination, partnership, and capital aid for infrastructure development.Maritime tourism development model in North Halmahera regency can be implemented in human resource, management, and more intensive promotion, community participa-tion and empowerment to create the integrated planning and management.